Literasi Keuangan Dan Locus Of Control Terhadap Perilaku Keuangan Komunitas Penggemar K-Pop Di Kota Padang - Dian Andini Putri; Tri Rachmat Riski (GLOBAL SCIENTS PUBLISHER, 2025)
Financial management is an activity that is consistently performed by every individual. Knowledge and understanding of the financial field are key factors in the effective management of finances. Financial literacy is a crucial element in the management of financial behavior, while locus of control plays a significant role in regulating wise financial behavior.The objective of this study is to determine the influence of financial literacy and locus of control on financial behavior among K-Pop fans in Padang City. The research utilizes a quantitative approach. The population in this study consists of K-Pop fans who are members of communities in Padang City. The sampling technique employed in this study is purposive sampling, with a total sample size of 175 respondents.The results of the study indicate that 1. Financial literacy has a positive and significant effect on financial behavior. 2. Locus of control has a negative and insignificant effect on financial behavior. 3. Both financial literacy and locus of control have a simultaneous effect on financial behavior.